Market Reaction Analysis of Annual Report Award Announcement: An Event Study Using Abnormal Return, Trading Volume Activity, and Stock Price - Fitri Astuti; Anggi Setya Prayoga (EkBis: Jurnal Ekonomi dan Bisnis, 2020)
This study intends to examine the differences in market reaction around the announcement of the Annual Report Award which is not only measured by abnormal return but is also measured using trading volume activity and stock prices. The data used are quantitative data in the form of a list of companies that received the Annual Report Award for the 2015-2018 period, the daily closing price of the ARA-winning company in the event window, the composite stock price index, the number of shares traded, and the number of shares outstanding. The event window is selected for 11 days because the long window period will blend with the effects of other events or confounding effects. The results of the study concluded that the market reacted around the announcement of the Annual Report Award for the 2015-2018 period measured using abnormal returns, trading volume activity, and stock prices. There is no difference in abnormal returns before and after the announcement of the 2013-2016 Annual Report Award period. Instead there are differences in trading volume activity and stock prices before and after the announcement of the Annual Report Award for the 2015-2018 period.